Prevalence and Determinants of Dropped Head Syndrome of Medical and Health Science Students: A Scoping Review - Valdez, Glenn Ford (Journal of Rural Community Nursing Practice, 2025)
Introduction: Students' constant use of digital resources has exacerbated neck ailments within a university setting, but the exact extent and reasons remain ambiguous. Aims: This review aims to consolidate evidence on prevalence, determinants, and interventions for use in policy frameworks. Methods: Seventeen empirical studies from January 2019 to May 2025 were included in the 350 studies screened. The researchers considered quantitative or mixed-methods studies focusing on TNS (Text Neck Syndrome), FHP (Forward Head Posturing), UCS (Upper Cross Syndrome), or other associated aches in the neck among tertiary students. Two reviewers charted the data, and themes from the data were derived. Results: The summary included fourteen cross-sectional surveys, two randomized controlled trials, and one mixed-methods thesis from nine countries in Asia, the Middle East, and Africa, with 7928 participants. Overall, prevalence ranged from 45% to 70%. The most extensive sample (n = 2,552, China) demonstrated UCS of 59.7%, while six medical colleges in Saudi Arabia reported TNS at 68.1%, with 19% having moderate-severe disability. Having four to five hours of screen exposure doubled to triple the risk. However, those with addiction-level behaviors elevated the odds nine-fold (adjusted OR=9.14) and disability (r=0.33) in comparison to non-affected peers. Conclusions: Psychosocial stress, alongside being female, consistently added to the susceptibility, while poor ergonomics and lower aerobic capacity provided the mechanical persuaders. Two culturally distinctive four-week exercise trials effectively reduced NDI scores by 60-90% and normalized cranio-vertebral angle.